Financial Constraints and Propagation of Shocks in Production Networks - Banu Demir Pakel; Beata Smarzynska Javorcik; Tomasz K. Michalski; Evren Ors (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This study finds that even small unexpected supply shocks propagate downstream through production networks and are amplified by firms with short-term financial constraints. The unexpected 2011 increase in the tax on imports purchased with foreign-sourced trade credit is examined using data capturing almost all Turkish supplier-customer links. The identification strategy exploits the heterogeneous impact of the shock on importers. The results indicate that this relatively minor, non-localized shock had a non-trivial economic impact on exposed firms and propagated downstream through affected suppliers. Additional empirical tests, motivated by a simple theory, demonstrate that low-liquidity firms amplified its transmission.
Keywords: F14; F61; G23; L14; E23; 330; production networks; shock transmission; financing constraints; liquidity